Are CD8 T cells involved in control of African trypanosomiasis in a natural host environment? - Sileghem, M.R.; Naessens, Jan (Wiley, 1995)
Murine models have suggested that CD8 T cells might play a major parasite-promoting role in African trypanosomiasis. To assess the role of these cells in a natural host environment, we have depleted CD8 cells from Boran cattle in vivo and subsequently infected these animals with Trypanosoma congolense by tsetse fly challenge. Following administration of a mouse monoclonal anti-bovine CD8 antibody, we have been able to achieve a depletion of more than 99.9% in peripheral blood, spleen, prescapular lymph nodes, prefemoral lymph nodes, mesenteric lymph nodes and Peyer's patches. Depletion could be maintained over a 4-5-week infection period. Despite the almost total absence of CD8 cells, no effect whatsoever was observed on parasitemia. In addition, anemia, which is the main factor determining the mean survival time in cattle was not affected by the CD8 depletion.